NEGOSIASI IDENTITAS PEREMPUAN MUSLIM HIJABERS COMMUNITY: STUDI KASUS PADA BRAND RIA MIRANDA - Listya Ayu Saraswati (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2019)
The rise of pious lifestyle among the middle class in Indonesia has emerged various expressions of pious identity. City areas with modern and dynamic lifestyles are now the contestation for urban identities. Middle class and urban living Muslim in Indonesia are the most active agent of representation in both production and consumption of culture and cultural products, such as fashion, and consequently become the trend setter for national and international Muslim living. By putting the focus on Muslim women in Hijabers Community, one of the most popular Muslim women organization in social media, I discuss the identity negotiation of Muslim women that is shaped and represented in Ria Miranda fashion brand. Ria Miranda, made by one of Hijabers Community founders, has been part of the community since its beginning in 2011. Ethnography study and in-depth interviews with Hijabers Community, Ria Miranda brand, and the consumers were conducted in Hijab Day events created by Hijabers Community from 2016 to 2019. Qualitative data were gathered and analyzed. In the result, I argue that Indonesia middle class urban Muslim women’s identity is continuously in ﬂux and negotiated in between the urban identity of becoming trendy, individualistic, and modern, and the pious Islamic identity of modest, communal accepted, and pious.